Koncentrácia poliovírusu typ 1 z potravín v modelovom experimente - Hucko, M (Ceskoslovenska epidemiologie, mikrobiologie, imunologie, 1990)
The author concentrated from contamined foodstuffs poliovirus type 1--vaccine strain--by means of negative pressure or overpressure filtration across membranes with a different porosity and by means of an ultracentrifuge. Foods - milk, meat, meat products and vegetables were contaminated by the virus so that various doses corresponded approximately to 1.2 or 4 PFU per gram of specimen. The virus in concentrates was detected on cell cultures on the Vero line by the plaque method. The virus extract (number of PFU expressed in per cent) from the originally inoculated or absorbed amount of the virus resp. was as follows: in negative filtration on average 53%, in overpressure filtration without the use of polyelectrolyte on average 75%, when using the polyelectrolyte 79% and when using utracentrifugation on average 87%.
Keywords: Food Microbiology; potravinářská mikrobiologie; Poliovirus